Predicting the lateral direction of deceptive and non-deceptive penalty kicks in football from the kinematics of the kicker - Lopes, J. E.; Jacobs, D. M.; Travieso, D.; Araujo, D. (Human Movement Science, 2014)
This study addresses the utility of the kinematics of penalty takers for goalkeepers in association football. Twelve professional and semi-professional players shot to one side of the goal with (deceptive condition) or without (non-deceptive condition) simulating a shot to the opposite side. The body kinematics of the penalty takers were registered with motion-capture apparatus. Correlation and regression techniques were used to determine the relation between the shot direction and aspects of the penalty taker`s kinematics at different moments. Several kinematic variables were strongly correlated with shot direction, especially those related to the lower part of the body. Some of these variables, including the angle of the non-kicking foot, acquired high correlations at time intervals that are useful to goalkeepers. Compound variables, here defined as linear combinations of variables, were found to be more useful than locally defined variables. Whereas some kinematic variables showed substantial differences in their relation to ball direction depending on deception, other kinematic variables were less affected by deception. Results are interpreted with the hypothesis of non-substitutability of genuine action. The study can also be interpreted as extending the correlation and regression methodology, often used to analyze variables defined at single moments, to the analysis of variables in a time continuous fashion.